Răspunsuri

Cel mai inteligent răspuns!
2014-06-14T11:14:07+03:00
2+4+6+........+2012=2(1+2+3+...........+1006)= 2* (1+1006)* 1006/2= 1007*1006

(1+3+5+...+2013)= (1+2013)* 1006/2=  2014*1006/2= 1007*1006

1007*1006-1007*1006=0
de unde ai (1+3+5+...+2013)= (1+2013)* 1006/2?
Eueeeu , raspunsul este 1+3+5+........+2013= n(n+1) : 2= 2013(2013+1):2
si a facut 2013:2 care este gresit !!!!!!!!!!
1+3+5+...+2013=1+2+3+...+2013-(2+4+6+....+2012)=2013*2014/2-1006*1007(cu formula lui Gaus)=2013*1007-1006*1007=1007(2013-1006)=1007*1007